Global value chains: a place for Mindanao producers? - Murray-Prior, Roy; Batt, Peter; Rola-Rubzen, Maria Fay; McGregor, Murray; Concepcion, S.; Rasco, E.; Digal, L.; Montiflor, M.; Hualda, L.; Migalbin, L.; Manalili, N. (ISHS, 2006)
The opportunity for a vegetable supply chain from Kapatagan in Mindanao, Philippines to compete in a globalised vegetable market was assessed using a pluralistic framework involving hard and soft systems methodologies. A dualistic model of the agribusiness system helped identify constraints and opportunities to improvements. Producers currently supply the 'price-driven' wet markets which are competitive and do not provide incentives for quality production. To enable change to occur improvements need to be made to infrastructure, land tenure and credit arrangements. In addition, alliances need to be developed between Mindanao producers, their cooperatives and supermarkets, food outlets and institutional buyers.